2021
DOI: 10.1007/s10854-021-06375-7
|View full text |Cite
|
Sign up to set email alerts
|

All-solution-processed environment-friendly solid-state BiOI photovoltaic cell with high-short-circuit current by successive ionic layer adsorption and reaction (SILAR)

Abstract: This research demonstrates a complete solution prepared environment-friendly high-performance solid-state BiOI photovoltaic cell with high-short-circuit current for the first time. All the layers have been prepared at room temperature in the atmosphere without using the vacuum process. The photovoltaic properties are improved with employing both electron transport layer (ETL) and hole transport layer (HTL) and with increasing the cycle number of the SILAR process up to 30 cycles where the maximum short-circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…The whole fabrication process was carried out in a dry nitrogen-filled glovebox. Finally, the colloidal graphite was spin-coated on top of the P3HT at 5000 rpm for 20 s and cooled in room temperature, followed by the deposition of Ag paste on colloidal graphite [17]. The whole process was repeated for different of CBI fraction at x=0, x=0.2, x=0.5, x=0.8 and x=1.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The whole fabrication process was carried out in a dry nitrogen-filled glovebox. Finally, the colloidal graphite was spin-coated on top of the P3HT at 5000 rpm for 20 s and cooled in room temperature, followed by the deposition of Ag paste on colloidal graphite [17]. The whole process was repeated for different of CBI fraction at x=0, x=0.2, x=0.5, x=0.8 and x=1.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…For the fabrication of carbon electrode, the colloidal graphite, displaying of the insulator tape and silver paste were done outside of the glove box. The purpose of using silver in Figure 7(i) is to provide a better and smooth connection between the I-V probe and the sample (Matiur et al, 2021). The overall full set of fabricated solar cells device structure is shown as in Figure 7(i).…”
Section: Methodsmentioning
confidence: 99%
“…A continuous compact film was obtained at a high speed, whereas a flaky structure was obtained at a lower speed (figure 4(d)); thus, the best PCE (0.39%) was achieved for a device containing continuous BiOI film. In another study, the same group employed an additional P3HT HTL and regulated the BiOI thickness [42,43]. All layers constructed of the device were fabricated using the solution-phase method [42], ultimately achieving a device with a highly improved PCE of 1.34% [42].…”
Section: Bioi Solar Cellsmentioning
confidence: 99%
“…In another study, the same group employed an additional P3HT HTL and regulated the BiOI thickness [42,43]. All layers constructed of the device were fabricated using the solution-phase method [42], ultimately achieving a device with a highly improved PCE of 1.34% [42]. In addition, they investigated the annealing temperature of the BiOI structure and found that it was transitioned to Bi 7 O 9 I 3 and Bi 5 O 7 I at 300 °C and 400 °C, respectively [44].…”
Section: Bioi Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation